Entrevista: Cecilia Iucci - Iucci, Cecilia; Alves, Guilherme (Participação, 2024)
Entrevista com Cecilia Iucci Universidad Nacional del Litoral, Argentina. (ciucci@unl.edu.ar) ORCID: https://orcid.org/0000-0003-0073-2124